Inovasi dalam Pembelajaran IPA Sumber Energi untuk Menumbuhkan Pemahaman Konsep Sejak Dini - Disa Sahra; Finda Rustiana; Airin Airin; Ari Suriani; Afriza Media (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This article aims to understand the concept of energy sources from an early age in order to increase their awareness of energy use and conservation. However, science learning in elementary schools (SD) often faces problems in delivering complex and abstract materials. This study investigates various innovations in science learning, especially those related to energy sources. In this study, we review the literature on various creative methods for learning, including the use of game media, blended learning, and interactive game tools. The results show that the implementation of these innovations can improve students' desire to learn and their learning outcomes. Therefore, science learning at the elementary level can be assisted by the integration of technology and appropriate learning approaches.